2019
DOI: 10.1016/j.celrep.2019.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genetic Characterization of Mitochondrial Ca2+ Uniporter Components Reveals Their Different Physiological Requirements In Vivo

Abstract: Summary Mitochondrial Ca 2+ uptake is an important mediator of metabolism and cell death. Identification of components of the highly conserved mitochondrial Ca 2+ uniporter has opened it up to genetic analysis in model organisms. Here, we report a comprehensive genetic characterization of all known uniporter components conserved in Drosophila . While loss of pore-forming MCU or EMRE abo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 41 publications
6
52
2
Order By: Relevance
“…Furthermore, we have also observed that one of the consequences of reactivating MAMs in our cell culture model was the increase of mitochondrial Ca 2+ uptake. Therefore, we decided to genetically manipulate Ca 2+ transport into the mitochondria by altering the expression of the mitochondrial Ca 2+ uniporter (MCU), since misexpression of MCU or of other components of the MCU complex has been shown to change the mitochondrial Ca 2+ content (Choi et al, 2017;Drago & Davis, 2016;K.-S. Lee et al, 2018;Tufi et al, 2019). We observed that MCU mRNA levels were not altered in frataxin deficient flies ( Figure S3A).…”
Section: Promotion Of Calcium Import Into the Mitochondria Recovers Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we have also observed that one of the consequences of reactivating MAMs in our cell culture model was the increase of mitochondrial Ca 2+ uptake. Therefore, we decided to genetically manipulate Ca 2+ transport into the mitochondria by altering the expression of the mitochondrial Ca 2+ uniporter (MCU), since misexpression of MCU or of other components of the MCU complex has been shown to change the mitochondrial Ca 2+ content (Choi et al, 2017;Drago & Davis, 2016;K.-S. Lee et al, 2018;Tufi et al, 2019). We observed that MCU mRNA levels were not altered in frataxin deficient flies ( Figure S3A).…”
Section: Promotion Of Calcium Import Into the Mitochondria Recovers Fmentioning
confidence: 99%
“…Regarding MCU downregulation, unexpectedly a strong silencing using a RNAi line triggered preadult lethality when co-expressed with the fhRNAi-1 line, whereas such lethality was not observed in the control cross. To bypass this problem, we decided to use a mutant allele of MCU (MCU1, described in (Tufi et al, 2019)) in a heterozygous configuration. 50% reduction of MCU expression in glia cells did not induce on their own any effect in the three parameters analyzed (negative geotaxis, brain integrity and lipid accumulation, (Figure S3C-I), and it is not able to suppress too the locomotor deficit of FRDA flies ( Figure 5A) and the brain vacuolization ( Figure 5B-E).…”
Section: Promotion Of Calcium Import Into the Mitochondria Recovers Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss-of-function mutations in MICU1 induce proximal myopathy, learning difficulties, movement disorder, fatigue, and lethargy in humans (Lewis-Smith et al, 2016; Logan et al, 2014) and deletion of Micu1 in mouse models causes perinatal lethality (Antony et al, 2016; Liu et al, 2016). Recently, genetic mutants were generated to characterize mtCU regulation in Drosophila (Tufi et al, 2019). Intriguingly, Tufi et al reported that a MICU1 loss-of-function mutation resulted in Drosophila lethality, which could not be rescued by a concurrent MCU loss-of-function mutation that completely ablated mitochondrial Ca 2+ ( m Ca 2+ ) uptake and subsequent mitochondrial permeability transition pore opening (Tufi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, genetic mutants were generated to characterize mtCU regulation in Drosophila (Tufi et al, 2019). Intriguingly, Tufi et al reported that a MICU1 loss-of-function mutation resulted in Drosophila lethality, which could not be rescued by a concurrent MCU loss-of-function mutation that completely ablated mitochondrial Ca 2+ ( m Ca 2+ ) uptake and subsequent mitochondrial permeability transition pore opening (Tufi et al, 2019). This observation suggests that the lethal phenotype of MICU1-null flies was not solely a result of aberrant mtCU-dependent Ca 2+ uptake.…”
Section: Introductionmentioning
confidence: 99%